1986
DOI: 10.1038/hdy.1986.61
|View full text |Cite
|
Sign up to set email alerts
|

The inheritance of style length in Oxalis rosea

Abstract: In Oxalis rosea it is found that some short-styled plants are dominant to non-short (mid-or long-styled plants) whilst others are recessive. Breeding experiments show that the short style form is under the control of two gene pairs (A, a and S, s) with shorts having either of the genotypes aaSS and aaSs. In plants segregating for A, a on an SS background, shorts appear as recessive whilst in plants segregating for S, s on an aa background, shorts appear as dominant. Among non-shorts, mids (MM, Mm) are dominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
2

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
4
0
2
Order By: Relevance
“…Even more difficult is the problem of the evolutionary origin of tristyly, although Charlesworth (1979) developed a 3-locus model for the origin and breakdown of tristyly. The model permits exploration of the effects of changes in pollinator effectiveness, rate of selfing, and inbreeding depression, and has been proven to be adequate for Oxalis rosea (Bennett et al, 1986).…”
Section: Source Of Variationmentioning
confidence: 99%
“…Even more difficult is the problem of the evolutionary origin of tristyly, although Charlesworth (1979) developed a 3-locus model for the origin and breakdown of tristyly. The model permits exploration of the effects of changes in pollinator effectiveness, rate of selfing, and inbreeding depression, and has been proven to be adequate for Oxalis rosea (Bennett et al, 1986).…”
Section: Source Of Variationmentioning
confidence: 99%
“…In contrast to O. alpina and related diploid species, considerable crossing over in O. valdiviensis is necessary to explain the segregation of long-styled progeny from shortstyled morphs with the M allele linked in repulsion (table 1 in Fyfe, 1950). Genetic control of tristyly diverges significantly in O. articulate Savgny, in which the S allele is recessive to the L allele (Fyfe, 1956;Bennett, Leach & Goodwin, 1986), and in O. tuberosa Molina, in which short-styled morphs consistently appeared in small numbers in the progeny of mid-脳 long-styled crosses, complicating interpretation of the genetic basis of style morph expression for this species (Trognitz & Hermann, 2001). Features of the genetic system controlling expression of tristyly in O. alpina are shared by species in Lythraceae and Pontederiaceae, in which S and M loci control expression of style morphs, the S locus is epistatic to the M locus, the loci may be linked or unlinked, and polyploidy occurs in some species (Fisher & Mather, 1943;Barrett, Morgan & Husband, 1989;Eckert & Barrett, 1993;Gettys & Wofford, 2008 Fisher (1941) developed equations to calculate the equilibrium frequencies of the mid-styled morphs with more than a single copy of the M allele in disomic, tetrasomic and hexasomic cases.…”
Section: Crosses With Long-styled Plantsmentioning
confidence: 99%
“…My colleagues have shown that three-or even four-gene models are needed for some species of Oxalis, and their elucidation is only just beginning (Bennett, Leach & Goodwins, 1986).…”
Section: Self-incompatibilitymentioning
confidence: 99%